Current Concepts of Surface Topography of Implants: A Review - Potdar, Raksha; Ramesh, Amitha (Journal of Health and Allied Sciences NU, 2021)
Both the rate of osseointegration and its extent depend upon the characteristics of the implant surface.12345 Depending on the surface of the implant determination of implant–bone contact area, the rate of bone formation around the implant can be done.6 Hence, the implant surface plays an important part in multiple ways in the osseointegration process.
Keywords: implants; osseointegration; surface topography